Progesterone Intramuscularly or Vaginally Administration May Not Change Live Birth Rate or Neonatal Outcomes in Artificial Frozen-Thawed Embryo Transfer Cycles - Liu, Yuan; Wu, Yu (Frontiers in Endocrinology, 2020)
Backgrounds: Previous studies suggested that singletons from frozen-thawed embryo transfer (FET) were associated with higher risk of large, post-date babies and adverse obstetrical outcomes compared to fresh transfer and natural pregnancy. No data available revealed whether the adverse perinatal outcomes were associated with aberrantly high progesterone level from different endometrium preparations in HRT-FET cycle. This study aimed to compare the impact of progesterone intramuscularly and vaginally regimens on neonatal outcomes in HRT-FET cycles. Methods: A total of 856 HRT-FET cycles from a fertility center from 2015-2018 were retrospectively analyzed. All patients had their first FET with two cleavage-staged embryos transferred. Endometrial preparation was performed with sequential administration of estrogen followed by progesterone intramuscularly 60mg per day or vaginal gel Crinone 90mg per day. Pregnancy outcomes including live birth rate, singleton birthweight, large for gestational age (LGA) rate, small for gestational age (SGA) rate and preterm delivery rate were analyzed. Student’s t test, Mann-Whitney U-test, Chi square analysis and multivariable logistic regression were used where appropriate. Differences were considered significant if p < 0.05. Results: No significant difference of live birth rate was found between different progesterone regimens (Adjusted OR 1.128, 95%CI 0.842, 1.511, p = 0.420). Neonatal outcomes like singleton birthweight (p = 0.744), preterm delivery rate (Adjusted OR 1.920, 95%CI 0.603, 6.11, p = 0.269), SGA (Adjusted OR 0.227, 95%CI 0.027, 1.934, p = 0.175) and LGA rate (Adjusted OR 0.862, 95%CI 0.425, 1.749, p=0.681) were not different between two progesterone regimens. Serum P level >41.82 pmol/L at 14 day post-FET was associated with higher live birth rate than serum P level ≤41.82pmolL in HRT-FET cycles when progesterone was intramuscularly delivered (Adjusted OR 1.690, 95%CI 1.002, 2.849, p = 0.049). But singleton birthweight, preterm delivery rate, SGA and LGA rate were not different between these two groups. Conclusions: Relatively higher serum progesterone level induced by intramuscular regimen did not change live birth rate or neonatal outcomes compared to vaginal regimen. Monitoring serum progesterone level and optimizing progesterone dose of intramuscular progesterone as needed in HRT-FET cycles has a role in improving live birth rate without impact on neonatal outcomes.